Influence of the interface temperature on the damage morphology and material transfer of C–Cu sliding contact under different current amplitudes - Wang, Hong (2023)
The influence of interface temperature on the damage characteristics of C–Cu contacts’ interface plays a critical role in the current-carrying friction process which occurs between the contact pairs. In this paper, a method is proposed to adjust the interface temperature via settling an external heat source. The damage morphology and material transfer of C–Cu contacts are focused on when the range of interface temperature varies from the room temperature (25 °C) to 300 °C. Based on the experimental results, it can be found that high interface temperature can inhibit the surficial erosion of carbon materials, which tends to be obvious, especially along with the increment of current. Moreover, both the delamination wear of carbon surface and the copper-to-carbon transfer behavior decrease with the thermal surge of interface. This beneficial effect of interface temperature results in the reduction in friction coefficient by 14.3%, whereas the negative impacts brought from the high interface temperature are the surface cracking and the rapid recovery of wear rate of carbon materials, under high-current condition.